The impact of self-regulated learning, personal knowledge management (PKM) skills, and English competency on university students' lifelong learning - Dinithambigai, Nadahrajan (2017)
Lifelong learning has been one of the most explored agenda in today's education field. Latest technology advancements and modern procedures as well provide new challenges for individual learners in their knowledge learning process. Therefore, people require to involve in the learning process consistently in their lifespan to adapt nature of changing environment of the information age to be ore competence and successful. There have been many empirical studies on lifelong learning in general. Consequently, this study is attempts to examine the abilities and competency of university students and their tendency on involving in lifelong learning. The theoretical framework of this research identifies three abilities of university students which influences the students lifelong learning. Those main three capability that influences the students lifelong learning are self-regulated learning, personal knowledge management skills and English competency accordingly. Overall, 380 students were participated in this correlational study. The analysis of this study considers the empirical literature, and the difference between independent and dependent variables. The findings of the research it has been found that all the predictors of the study have significant relationship with students' lifelong learning. The paper also makes recommendations for future research.